Interactive Method “Mindless Attack” And Methods Of Its Effective Use - Shukurova Sevinch Durbekovna (Zien Journals, 2025)
In order to increase the effectiveness of education, the article discusses the importance of using modern interactive methods in the educational process and elaborates comprehensive information and recommendations
Keywords: “Brainstorming”; interactive method; useful methods